Strategi Pengelolaan Emosi Anak melalui Bermain Peran Makro di Taman Kanak-Kanak Intan Payong, Banda Aceh - Sri Mardiana; Dewi Fitriani (Journal of Islamic Education Students (JIES), 2026)
This study aims to describe the implementation of the macro role-playing method as an effort to support emotional regulation in early childhood. The research employs a qualitative approach with a descriptive design. The study was conducted at Intan Payong Kindergarten, with role-play center teachers as the research subjects. Data were collected through observation, interviews, and documentation to obtain an in-depth understanding of the implementation process of the macro role-playing method. Findings reveal three main strategies for children's emotional management: (1) organization through four structured scaffoldings and play rules; (2) delivery through contextual thematic scenarios, varied media, and emotional language modeling; and (3) classroom management through calm behavior modeling, gentle persuasive communication, and interactive conflict mediation. Continuous evaluation through behavioral observation indicates the method effectively helps children recognize, express, and control emotions in social situations. These findings contribute to understanding emotional development strategies in Islamic early childhood education.